Burst Signal Detector based on Signal Energy and Standard Deviation - Stasionis, L.; Serackis, A. (Elektronika ir Elektrotechnika, 2014)
Paper focuses on the spectrum sensing for cognitive radio solutions. The new algorithm is proposed for burst signal detection in frequency band where only this type of primary user signal appears (e.g. GSM band). Proposed spectrum sensor use signal energy and standard deviation estimates for primary user signal detection. A single perceptron is proposed to define a threshold for spectrum sensor. To investigate the efficiency of proposed spectrum sensor the real environment measurements were performed in the frequency band used by GSM system for downlink. An additional analysis of the signal energy estimates showed the periodicity of the energy changes in time domain. The calculation of FFT for signal energy changes in time has proven the performance of proposed spectrum detector for low power (situated far away from spectrum sensor) primary user signal detection in situations where it is covered by environment noise. DOI: http://dx.doi.org/10.5755/j01.eee.20.2.6384